2017
DOI: 10.1016/j.ygyno.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with deciding between risk-reducing salpingo-oophorectomy and ovarian cancer screening among high-risk women enrolled in GOG-0199: An NRG Oncology/Gynecologic Oncology Group study

Abstract: Objectives Women at increased genetic risk of ovarian cancer (OC) are recommended to have risk-reducing salpingo-oophorectomy (RRSO) after completion of reproductive planning. Effective screening has not been established, and novel screening modalities are being evaluated. Methods Participants chose either RRSO or a novel OC screening regimen (OCS) as their risk management option, and provided demographic and other data on BRCA mutation status, cancer worry, perceived intervention risks/benefits, perceived c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 42 publications
(33 reference statements)
3
18
0
Order By: Relevance
“…However, the reliability of the evidence is very low, and the authors could not draw definitive conclusions. Mai et al [13] found that concerns about menopausal symptoms and loss of fertility, and the perception that “surveillance was less invasive and radical than surgery,” were associated with a higher likelihood of choosing OC surveillance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the reliability of the evidence is very low, and the authors could not draw definitive conclusions. Mai et al [13] found that concerns about menopausal symptoms and loss of fertility, and the perception that “surveillance was less invasive and radical than surgery,” were associated with a higher likelihood of choosing OC surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…However, many factors can influence the carrier’s decision-making process [3,7] and “a posteriori” satisfaction with her own choice. Such factors might be psychological (as perceived cancer risk [5,8,9], anxiety in carrier with a previous BC [6] or body image perception [10,11]); related to surgical procedure (as in the case of expected [12,13] or unexpected side effects [14]); or linked to carriers’ quality of life, fertility, and sexuality [15,16,17,18,19]. Unfortunately, previously published studies are often focused on single aspects of the Risk-Reducing procedures in high-risk women [6,12,15,20,21,22,23,24] and composed of heterogeneous populations (high-risk women or BRCA carriers and women with previous breast cancer).…”
Section: Introductionmentioning
confidence: 99%
“…The survey also discovered that the majority of respondents (58.7%) thought women with BRCA mutation should be offered with PGD as a choice. However, only 34.8% of respondents would consider undergoing PGD themselves to reduce the risk of transmitting the mutation to their offspring [110]. Moreover, PGD involves discarding normal embryos and this may not be acceptable from an emotional, religious, or ethical point of view [111].…”
Section: Psychosocial Evaluation Before Fertility Preservation and Prmentioning
confidence: 99%
“…To assess effects of identified cancer burden, a large Gynecologic Oncology Group (GOG) trial evaluated 2287 questionnaires in high risk women that measured worry, perceived cancer risk, risks vs. benefits, and quality of life. The more invasive RRSO option, which 40% of the participants chose, was associated with higher perceived risk and worry [ 68 ]. Half of all the participants estimated their lifetime ovarian cancer risk to be >50%, which is greater than the actual risk.…”
Section: Psychosocial Stress Of Brca Mutation Carriersmentioning
confidence: 99%